'Out of the Air': Judith Weir's Emergence in 1970s Britain, or Interpreting Creative Self-Censorship. Issue 3 (3rd December 2019) - Beard, David
Abstract: Most accounts of Judith Weir's music focus on her mature, apparently postmodern approach. By contrast, my analysis of the early withdrawn works highlights a series of creative dialogues with some of Weir's older British and Continental contemporaries, and more historical models. These interactions reveal that modernism and the avant-garde were essential to the evolution of Weir's musical language—a formative experience that has been downplayed in attempts by critics to distance Weir from modernism. The gendered reception of Weir's music is also noted, in which her natural modesty and withdrawal of early works have been portrayed as symptoms of feminine uncertainty, self-criticism, and anxiety. This discourse is recalibrated by relating it first to creativity theories, in which dialogue, uncertainty, and serendipity are valued, and second to the more widespread practice of withdrawing works, which illustrates how self-censorship is a common and vital part of creative practice, irrespective of gender.